Occupational exposure to solar ultraviolet radiation among outdoor workers in Lisbon, 2023—first results of the MEAOW study - Carvalho, Fernanda; Strehl, Claudine; Barroso-Dias, Jorge; Castela, Maria Miguel; Gobba, Fabriziomaria; Lapão, Luís Velez; Loney, Tom; Maia, Mélanie Raimundo; Modenese, Alberto; John, Swen Malte; Rodrigues, Ana; Pinho, Cristina; et al. (Frontiers in Public Health, 2025)
IntroductionSolar ultraviolet radiation (UVR) exposure is the primary external factor associated with the development of skin cancer. Accurate, valid, and reliable objective estimates of individual UVR exposure are required to quantify the risk of skin cancer in outdoor workers. Such data can be used to develop and implement policies and practices to reduce, or at least manage, UVR exposure in outdoor workers. Currently, there is a dearth of objective exposure data for many countries. Lisbon, as a low-mid-latitude region (38°46′ N), experiences a high UV Index (UVI) for a long period of the year, increasing the potential risk of skin cancer among outdoor workers in Portugal. This is the first study to objectively measure personal solar UVR exposure among outdoor workers in Portugal.MethodsThis study used a prospective observational design during seven consecutive months (April to October 2023) studying personal UV exposure of Asphalthers, Gardeners, Gravediggers, Pavers, and Sanitation Workers. Measurements of personal exposure were conducted using the GENESIS-UV measurement system, and ambient solar UVR data was estimated Jm−2 utilizing a UV-Biometer radiometer.ResultsPersonal hourly and daily doses measured by the GENESIS-UV measurement system were lower than the solar irradiation measured on a horizontal surface by the UV-Biometer radiometer. Gravediggers and Gardeners showed in average, the highest monthly daily averages (250 Jm−2 and 266 Jm−2, respectively). The maximum monthly daily average occurred for Gravediggers in the month of April (363 Jm−2). Pavers recorded the lowest solar UVR average daily doses (62 Jm−2). Sanitation Workers recorded the highest average daily dose (837 Jm−2, July 7th). The maximum single dosimeter value was accumulated by Gravediggers (1,097 Jm−2, May 9th).DiscussionThis study measured solar UVR exposure in important occupations not so often studied. The ICNRIP occupational limit value of 133 J/m−2 was surpassed in all occupations except the Pavers. These results showcase that the design of adequate prevention campaigns for preventing occupational skin cancer in outdoor workers should include personalized exposure risk messaging in the future.